Microeconometric Evidence of Financing Frictions and Innovative Activity - Amaresh K. Tiwari; Pierre Mohnen; Franz Palm; Sybrand Schim van der Loeff (Center for Economic Studies and ifo Institute (CESifo), 2014)
Using Dutch data we empirically investigate how financing and innovation vary across firm characteristics. We find that when firms face financial constraints, debt financing and innovation choices are not independent of firm characteristics, and R&D slows down. In the absence of financial constraints, however, as they raise debt, firms become less inclined to innovate and the change in the propensity to innovate no longer varies with firm characteristics. We find that financing constraints faced, propensity to innovate, and R&D intensity are not uniform across firm characteristics. A new "control function" estimator toaccount for heterogeneity and endogeneity has been developed.
Keywords: G30; O30; C30; 330; innovation; R&D; capital structure; financial constraints; firm characteristics; correlated random effects; control function; expected a posteriori